The Learning of Origins and Significance of Lanna’s Yee Peng Festival and Thai’s Loy Krathong Festival Through Anthropological and Archaeoastronomical Perspectives - Saelee, Cherdsak; Riyaprao, Orapin; Sriboonrueang, Korakamon; Komonjinda, Siramas (Journal of Inclusive and Innovative Education, 2022)
This paper investigates the origins and significance of Lanna’s Yee Peng Festival and Thai’s Loy Krathong Festival in terms of anthropological and archaeoastronomical aspects. According to anthropological studies, two ethnic groups migrated and then settled in the region of modern-day Thailand: (1) the Tai people migrated from China into the northern region, Lana Kingdom; (2) the Mon people migrated from ancient Kalinga (now the Orissa state of India), into the central region as well as the ancient Khmer Kingdom. Both groups of settlers carried along with their beliefs, religions, traditions, languages, and calendrical systems. We find that the Lanna Tai people name their calendar years as “Mother-Child” years (Mae Pee-Look Pee) in the Hontai system, which is similar to the “Stems-Branches” in the sexagenary cycle of China during the Eastern Han dynasty. During the Han dynasty, all beliefs, religions, including traditions and norms were influenced by Confucianism and Taoism. The worship of the Deity of Water, expressed through the Xiayuan Festival, is set to celebrate on the full moon day of the 10th Chinese lunar month that coincides with the 12th Thai lunar month or Thai’s Loy Krathong Festival. This day on the full moon day of Krittika was previously regarded as the New Year Eve according to the Saka calendar during the period of Sukhothai, Ayutthaya, and the ancient Khmer kingdoms. We apply archaeoastronomy involving lunar mansions, zodiac signs, and constellations to study why the full moon day of Krittika was related to the New Year Festival in ancient times. We find that before the Vedic age (1500 – 600 B.C.), the Autumnal Equinox had been set to the day a full moon residing in the Krittika Nakshatra (the Pleiades) while the sun entering into Vrishchika Rashi (Scorpio). In addition, we find that the word “Loy Krathong” was first used in King Rama III of the Rattanakosin era. Early in the Sukhothai era, the festival literally was called “Phao Tien Len Fai.” The lotus shape floater (Krathong) used to worship the Hindu Goddess of water (Phra Mae Khongkha) nowadays results from mixed beliefs from Taoism, Chinese Buddhism, and Hinduism’s Bali Jatra Festival from Kalinga. More importantly, local astronomical wisdom has used the full moon of the 12th lunar month to align the Thai lunar calendar to the solar calendar from ancient times until the present days.